Clinical and echocardiographic profile and outcomes of peripartum cardiomyopathy: the Philippine General Hospital experience. Issue 1 (28th November 2013) - Samonte, Vim I; Ngalob, Queenie G; Mata, Ghea Divina B; Aherrera, Jaime Alfonso M; Reyes, Eugene; Punzalan, Felix Eduardo R
Abstract : Background: Peripartum cardiomyopathy (PPCM) is a rare disease entity of unknown aetiology. High rates of mortality or poor overall clinical outcome are reported in women with this condition. Certain characteristics are risk factors for this disease. In Asia, there are limited data, especially in the Southeast Asian region. In the Philippines, no data exist regarding the prevalence or risk factors. Objectives: To determine the prevalence, profile and outcomes of PPCM in Philippine General Hospital and to describe their echocardiographic findings. Methods: All patients diagnosed with PPCM in the period of 1 January 2009–31 December 2010 were seen and examined. Demographic data and echocardiogram of the patients were reviewed. Results: 9 were diagnosed with PPCM during the study period. The prevalence is 1 in 1270 live births. Mean age was 29. 78% presented with moderate to severe heart failure symptoms in the prepartum period. Among purported risk factors for PPCM, obesity, multiparity and pre-eclampsia were seen in most. Conversely, only one patient admitted to having more than a single sexual partner. Only one patient had multifetal pregnancy. None were smokers. 44% underwent caesarean section for maternal indication. No mortality was seen. Fetal outcomes were good with all resulting in live births and most were appropriate for gestational age. Echocardiographic findings showed global wall motion abnormalities in the majority, mean ejection fraction of 34% and mean fractional shortening of 20%. Conclusions: PPCM is rare in the Philippines. Compared with international data, our patients are younger with low percentages of promiscuity, multifetal pregnancy, smoking history and tocolytic use. Similar to previous studies, obesity, multiparity and pre-eclampsia were also present in our PPCM patients. Immediate maternal and fetal outcomes were generally good. Adherence to standard heart failure management is high.